Psychology applied to everyday life - Gardner, Rick M. (Wadsworth/Thomson Learning, 2002)
In this [book, the author] creates a personalized, interactive environment focused not only on psychological theory and research in the field, in the lab, and online, but on the practical applications available to [one] everyday. What accounts for achievement in one individual but not in another? What are the influences of the media on modern violence and political aggression? on personal attraction, the changing nature of the family, and individual health? Readers are encouraged to think critically, to analyze, and to challenge their own misconceptions. -Back cover.